Anion-site-modulated thermoelectric properties in Ge2Sb2Te5-based compounds - Hu, Ping; Wei, Tian-Ran; Huang, Shao-Ji; Xia, Xu-Gui; Qiu, Peng-Fei; Yang, Jiong; Chen, Li-Dong; Shi, Xun (Rare metals, 2020)
The amalgamation of multi-subjects often elicits novel materials, new concepts and unexpected applications. Recently, Ge 2 Sb 2 Te 5 , as the most established phase-change material, has been found to exhibit decent thermoelectric performance in its stable, hexagonal phase. The challenge for higher figure of merit ( zT ) values lies in reducing the hole carrier concentration and enhancing the Seebeck coefficient, which, however, can be hardly realized by conventional doping. Here in this work, we report that the electrical properties of Ge 2 Sb 2 Te 5 can be readily optimized by anion-site modulation. Specifically, Se/S substitution for Te induces stronger and more ionic bonding, lowering the hole density. Furthermore, an increase in electronic density of state is introduced by Se substitution, contributing to a large increase in Seebeck coefficient. Combined with the reduced thermal conductivity, maximum zT values above 0.7 at 800 K have been achieved in Se/S-alloyed materials, which is ~ 30% higher than that in the pristine Ge 2 Sb 2 Te 5 .